Perancangan Sistem Penggajian Karyawan Berbasis Website PT. Layangan Putus - Hotmaida Simanjuntak; Riris Lima Putri; Aries Saifudin; Yulianti Yulianti; Munawaroh Munawaroh (Teknik Informatika Universitas Pamulang, 2022)
PT Layangan Putus is a company that operates in the electronics section, especially producing CCTV and other equipment. In the process of work PT. Layangan Putus are still lacking in terms of the payroll process because they still use the manual method. Therefore, a more efficient website-based payroll system was designed in order to facilitate the payroll process of PT. Layangan Putus for employees. Payroll is a reward given to employees to move employees to work in a company. The use in this method is Waterfall. In this method, in addition to simplifying the performance of employee salary-based input, it also helps in minimizing an error in calculating employee salaries.